Comparison of the reactivity of [2.2]paracyclophane and p-xylene - Dyson, P; Humphrey, D; McGrady, J; Mingos, D; Wilson, D (1995)
The relative abilities of [2.2]paracyclophane (C16H16) and p-xylene (C6H4Me2-1,4) to form arene tricarbonyl complexes from chromium hexacarbonyl has been studied in dioxane using the Strohmeier reflux method, and the rate constants contrasted. The reactions are found to proceed more quickly with [2.2]paracyclophane by ca. 25%. Density functional molecular-orbital calculations have rationalised this observation, and indicate that the enhanced reactivity of the [2.2]paracyclophane system relative to p-xylene is a consequence of repulsive interactions between the two arene decks in the former, which are relieved to some extent by co-ordination of the electron-withdrawing Cr(CO)3 fragment.